2012
DOI: 10.3810/pgm.2012.09.2596
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Stimulant Medication to Treat Neurocognitive Deficits in Patients with Pediatric Cancer, Traumatic Brain Injury, and Sickle Cell Disease: A Review

Abstract: Several chronic health conditions of childhood, including pediatric cancers, traumatic brain injury (TBI), and sickle cell disease (SCD) are associated with significant neurocognitive impairments that can compromise educational attainment and future vocational opportunities. The prominence of attentional deficits as part of the neurocognitive sequelae associated with each of these conditions has led some researchers to draw parallels with another chronic condition that manifests in childhood, specifically the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Screening for asthma and asthmatic medication is routine during neurodevelopmental evaluations, as certain asthma medications can reportedly cause increased heart rates and behavioral issues similar to hyperactivity. 15 Children with asthma are also thought to be at higher risk for ADHD in the general pediatric population, though the evidence is conflicting. [16][17][18][19][20] In addition, both disorders are quite common in this group; 30% to 70% of patients with SCD have asthma, while one study found that 51% of children with SCD had behavioral and emotional issues per parental and teacher report.…”
Section: Discussionmentioning
confidence: 99%
“…Screening for asthma and asthmatic medication is routine during neurodevelopmental evaluations, as certain asthma medications can reportedly cause increased heart rates and behavioral issues similar to hyperactivity. 15 Children with asthma are also thought to be at higher risk for ADHD in the general pediatric population, though the evidence is conflicting. [16][17][18][19][20] In addition, both disorders are quite common in this group; 30% to 70% of patients with SCD have asthma, while one study found that 51% of children with SCD had behavioral and emotional issues per parental and teacher report.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulants do not appear to increase seizures in the typical population, children with refractory epilepsy, nor our subset of SWS subjects 15,16 . While stimulants are widely used in other pediatric chronic diseases, efficacy and safety data of stimulants has not be comprehensively studied in cancer, traumatic brain injury, or other neurovascular disorders such as sickle cell disease 17 . One recent crossover controlled trial in 14 subjects with sickle cell disease and a history of stroke showed improved attention ratings; more important, in this subset of patients with known cerebrovascular disease, no serious side effects were noted 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Although further studies are needed, those that have assessed the incidence of side effects have generally confirmed that the exacerbation of symptoms is mild, dose dependent, and typically does not lead to medication discontinuation 2,25,36,78 (Tables 2 and 3). 12,14,18,24,25,34,52,60,66,74 The use of stimulant medications for PPCS neurocognitive deficits should be used with caution or not considered in patients presenting with symptoms including somatic (headaches, loss of appetite), vestibular/visual (dizziness), and/ or a head injury that was instigated by potential cardiogenic pathology (eg, syncopal episode). While the adverse effects of stimulant medications are rare, dizziness, headaches, and cardiac-related events have been reported.…”
Section: Safety/adverse Effectsmentioning
confidence: 99%
“…Although further studies are needed, those that have assessed the incidence of side effects have generally confirmed that the exacerbation of symptoms is mild, dose dependent, and typically does not lead to medication discontinuation 2,25,36,78 (Tables 2 and 3). 12,14,18,24,25,34,52,60,66,74…”
Section: Efficacy Of Stimulants In Mtbimentioning
confidence: 99%